Consistent Maintenance Management Model: Results of changes of maintenance organisation structure and processes - Sailer, Jan; Hladík, Tomáš (Manufacturing Technology Journal, 2021)
A number of asset management models, methodologies and tools are available and well known today. How-ever, various organizational approaches to asset management processes are adopted by companies in the industry. In the paper, a number of examples of maintenance process models are summarized and a comparison of examples (benchmark) of real maintenance organizational structures is presented. The used examples origin from chemical, petrochemical and automotive industries. On this background, a case study of major maintenance organization change in Unipetrol, a central European refinery and petrochemical group (part of PKN Orlen) is presented and analysed. The goal of the implemented changes in the company was to increase the overall efficiency of the maintenance organization, mainly in the areas of management, and to achieve the set KPIs. Organizational changes were implemented on the basis of a model of a close connection between maintenance and production organizations in the form of a Multi-profession production team, named "Facility team". The changes in the organisational structure and asset management processes described in the paper had finally a significant impact on the number of management positions (reduction by 25%), roles, competencies and asset management process flow. The quantitative impacts to KPIs in areas fulfilment of process safety requirements and efficiency, after implementation this changes, it had a positive effect in the horizon of the coming year and are also evaluated and analyzed in the paper.
Keywords: Maintenance organization; Facility team; Maintenance KPI; Maintenance management